Toward a dynamically balanced cluster oriented DHT - Rufino, José (2004)
In this paper, we present a model for a cluster oriented Distributed Hash Table (DHT). It introduces software nodes, virtual nodes and partitions as high level entities that, in conjunction with the definition of a certain number of in variants, provide for the balancement of a DHT across a set of heterogeneous cluster nodes. The model has the following major features: a) the share of the hash table handled by each cluster node is a function of its enrollment level in the DHT; b) the enrollment level of a cluster node in the DHT may change dynamically; c) cluster nodes are allowed to dynamically join or leave the DHT. A preliminary evaluation proved that the quality of the balancement of partitions of the hash table across the cluster, measured by the stan dard deviation with relation to the ideal average, surpass the one achieved by using another well known approach.